Amazigh/Berber Literary and Historical Studies: Approaching Colonial Humanities from the Perspective of Critical Humanities - (:unkn) unknown (My University, 2021)
Amazigh/Berber Researchers, schoolteachers, students, and writers from the Amazigh/Berber region of Kabylia in northern Algeria made use of colonial knowledge, autobiographical data, and oral sources to revise and to subvert colonial humanities. They contributed to a chain of studies leading to the demise of presuppositions and interpretations of colonial humanities in Berber studies. Though often unrecognized, Kabyle intellectuals “coproduced” as well as challenged colonial literary and historical research. I argue that instead of considering early Kabyle intellectuals as reproducing the “mythologies” of colonial studies, other concepts such as acquisition, discussion, appropriation, and coauthorship are more appropriate. In the field of literary studies in Africa, the example of Kabyle intellectuals points to seemingly universalist humanities as locally bounded and invites reflection on both decolonizing African studies and “provincializing” the general disciplines.
Keywords: African Research